Fotografia, comunicação e ciência: trajetórias históricas e ações para a compreensão do conhecimento científico - Silva, Janinne Barcelos de Morais (2015)
Evaluating frequent discussions about the social counterpart of science and the need for its popularization, we investigated the use of Photography as a facilitator and mediator feature in the process of construction of knowledge, among the general public. Our goal was to investigate how these images can be used to popularize the researchs; what is their role in the construction of scientific knowledge; and how the scientific community associated with it, can approach large public without compromising the integrity of the information. Our hypothesis is that scientific texts, associated with photography, have major possibility to spark the interest of general public and facilitate the understanding of the information. To test this hypothesis, we expanded the discussions on science social relations and Scientific Communication. Checking in the field, we used quantitative research, such as questionnaires and semistructured interviews; and, also, the method of measuring eyes movements, known as Eye tracker. This technique allowed us to observe the behavior of respondents while reading the text and the photographs, and collect important metrics to evaluate their attention, such as the duration, the route and the location of their look. Given the results, we observed that inter-relationship between scientific text and photography can build a privileged way in the search for understanding of science and consequent formation of knowledge.